Relationship between body image and breast self-examination intentions and behavior among female university students in Malaysia - Abu Samah, Asnarulkhadi; Ahmadian, Maryam (Asian Pacific Organization for Cancer Prevention, 2014)
This study aimed to examine the relationship between body image satisfaction and breast self-screening behaviors and intentions. The sample for this cross-sectional study consisted of 842 female university students who were recruited from a number of public and private universities. Data were obtained between the months of November and December, 2013, using multistage random cluster sampling. Main research variables were breast cancer screening behavior and intentions, demographic factors, and the total scores on each of the Multidimensional Body-Self Relations Questionnaire (MBSRQ-Appearance Scales) subscales. Results of multivariate analysis showed that having higher satisfaction and more positive evaluation of appearance were related to having performed breast self-examination more frequently in the last year and intending to perform breast self-examination more frequently in the next year. Longitudinal research can potentially provide detailed information about overall body image satisfaction and breast cancer screening behavior among various communities.